Evaluation of the effects of green forage clipping on grain yield and its components in double crop of Iranian oat cultivars - Pirbalouti, Abdollah Ghasemi; Hematzadeh, Farshid (MTT, 2004)
In order to study the dual-purpose use of oat and the effects of clipping at different growth stages on grain yield and some other characters of oat and Maquee barley, an experiment was conducted in educational field of Jihad- Keshavarzei Education Center of Shahrekord in 2000-2001. The experimental was split plot in randomized complete block design with three replications. Three clipping treatments; harvest after 5 and 10 cm growth and a non harvest (control) were assigned as factor A in sub plots, and five lines of oats (No: 2, 17, 28, 32 and 36) and Maquee barley (control) as factor B in sub plots. Clipping effects were significant on all traits except number of grain and number of tillers. Delay in harvest decreased straw yield, grain yield, biological yield, plant height, total number of fertile tiller and 1000- weight grain, while duration sowing to maturity and sowing to heading and forage yield increased. There were significant differences among lines in plant heigh, duration sowing to maturity, sowing to heading, forage yield, grain yield, biological yield, number of grains, harvest index and number of tillers. Lines No. 2 and 17 had the highest grain and biological yields and had faster growth, while lines No. 28 and 32 had a low forage yield, grain yield and biological yield and due to their slow growth rate were not suitable for this region. There were significant interaction effects between clipping and line for plant height and grain yield. It was concluded that clipping in 2 and 17 lines could be done in other to supply the forage for livestock without any adverse effects on yield. Christian, S. et al. 1989. Agronomy Journal 81:145-150; Dunphy, D. J. et al. 1982. Crop Science 22:106-109; Pumphrey, F. V. 1970. Agronomy Journal 62: 641-643, Redmon, L. A. et al. 1995. Agronomy Journal 87: 137-147; Sharrow, S. H. and Motazedian, I. 1987. Agronomy Journal 79: 502-504; Winter, S. R., et al. 1990. Agronomy Journal 14: 415-421.
Keywords: Ka; clipping; components yield; double crop; grain yield; lines of oat